What are four-year-olds doing at school? : reconciling current knowledge about learning in young children with early educational pedagogy - Hayes, Nóirín (Trinity College (Dublin, Ireland). School of Education, 2004)
The study addresses the question of four-year-olds at school on two levels. On the one hand, the study describes what four-year-olds are doing at school. Using data from the IEA Pre-primary Project the author provides information on parental and teacher expectations for 203 four-year-olds and presents details of the observed behaviour of the children and their teachers in school. Some of this data has been reported elsewhere (Hayes, O'Flaherty and Kernan, 1997). Substantial additional analysis has been carried out to provide greater detail on social interactions in the classrooms including matrices to allow for an examination of the degree of match between teacher planning and child behaviour. In addition to the direct question of what Irish four-year-olds actually do at school the thesis also considers the question of whether four-year-olds should be in primary school. In this connection it presents, analyses and discusses the child activities recorded, the observed adult behaviour and the management of time in the classroom in the context of an extensive review of psychological and educational research.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin